SOCIAL INTERACTION AND RELATIONSHIPS OF INDIVIDUALS IN THE COMPOSITION OF TECHNOLOGY - Muratova, I. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
The purpose of the article is to reveal technology as a human activity in which people engage in such interaction with each other and build such relationships and social ties that are mediated by technical means and ensures success in the process of realizing a common goal. To overcome the limitations of narrowly specialized ideas about technology, the research is based on the scientific methods and theoretical principles of social philosophy. This approach allows us to understand technology as a universal principle of social practice, not just production. The need for a philosophical reflection of the immanent connection that exists between technology and sociality is proved by the author. Therefore, the author offers understanding of technology as unity of scientific and technical means and forms of social interactions in subjective practice and objectification human intentions and goals. The results of such research contribute to the establishment of the scientific and theoretical foundations of the practice of management of innovations and technologies with the purpose of conscious humanistic direction of scientific and technological progress.